True or False Game-Based Learning Strategy to Enhance the Socio-Emotional Skills of Elementary School Students - Dewi, Adelia Nurvita; Wulandari, Murfiah Dewi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to fill the research gap regarding the socio-emotional impact of the True or False learning strategy by evaluating its effect on elementary school students' socio-emotional development. Methodology: A quantitative approach with a quasi-experimental design involving two groups (experimental and control) was employed. The normality of the data was tested using the Shapiro-Wilk method, and homogeneity was assessed to ensure equal variance between the groups. A t-test was conducted to determine the significance of the intervention's impact. Results: The data were found to be normally distributed and homogenous across both groups. The t-test results showed a significant improvement in the socio-emotional skills of the experimental group (Sig. = 0.000) compared to the control group (Sig. = 0.013). This supports the alternative hypothesis (H₁), indicating that the True or False strategy is effective in enhancing socio-emotional abilitie. Applications/Originality/Value: This study introduces a novel application of the True or False strategy, which has traditionally been used to improve cognitive and critical thinking skills. Its implementation in developing students’ socio-emotional competencies represents a new and valuable contribution to educational practices, particularly at the elementary school level.